HAPPINESS REPRESENTED IN THE POEM FORESIGHT BY WILLIAM WORDSWORTH - Barda, Toha; Saprudin, Saprudin (Universitas Suryakancana, 2023)
The research was aimed at describing happiness represented in the poem â€œForesightâ€ by William Wordsworth. The happiness on the poem was analysed through characters, figurative languages, and imageries that built the poem. The research was conducted by means of descriptive qualitative research method with objective approach. The data of the research were words and phrases obtained from lyrics on the poem. The data were then collected and analysed. The techniques of analysing data applied were reducing, presenting and drawing conclusion. The results of the research show that there are three figurative on the poem â€œForesightâ€ by William Wordsworth, such as metaphor, simile, and personification. Meanwhile, the imageries acquired from the poem â€œForesightâ€ by William Wordsworth are kinesthetic imagery, visual imagery, auditory imagery, and tacticle imagery. Furthermore, the poem â€œForesightâ€ by William Wordsworth represents happiness in the form of the beauty nature such as flowers and strawberry gardens.